Dentin–Pulp Complex Response in Molars of Rats after Occlusal and Cervical Restorations with Conventional Glass Ionomer Cement and Nano-Hydroxyapatite Silica Glass Ionomer Cement - Fayez Hussain Niazi; Norhayati Luddin; Masitah Hayati Harun; Arshad Hasan; Thirumulu Ponnuraj Kannan; Suharni Mohamad; Amer Mahmood (Applied Sciences, 2023)
The purpose of this in vivo study was to evaluate and compare the dentin–pulp complex response following occlusal and cervical restorations in rat molars restored with nano-hydroxyapatite silica glass ionomer cement (nano-HA-SiO2-GIC) and conventional glass ionomer cement (c-GIC). In total, 64 maxillary first molars of 32 male Wistar rats were restored using Fuji IX (c-GIC) and nano-HA-SiO2-GIC using a split-mouth design. Half of them were reserved for the occlusal type of restoration while the other half was for cervical restorations. After one week and one month, rats were euthanized and were stained with hematoxylin and eosin, Masson’s trichrome, and Brown and Brenn techniques for histological examination. Parameters such as disorganization of the pulp tissue, inflammatory cell infiltration, detection of bacteria, and tertiary dentin deposition were measured for each group. One week after sacrifice, the odontoblastic layer was disrupted, and moderate inflammation in the pulp area close to the cut dentin was observed in both types of restorations. Nano-HA-SiO2-GIC showed significantly superior properties when assessed based on tertiary dentin formation as compared to c-GIC. One month after sacrifice, there was no evidence of disruptions of the odontoblast layer, which exhibited a normal palisade appearance in both groups. In terms of inflammation, the pulp tissue recovered in almost all cases except one of c-GIC, but a few cases of the nano-HA-SiO2-GIC group still displayed mild-to-moderate inflammatory reactions, especially of the occlusal type. Both c-GIC and nano-HA-SiO2-GIC exhibited favorable responses in terms of biocompatibility. Nano-HA-SiO2-GIC exerted more inflammation but encouraged better tertiary dentin formation compared to c-GIC.